Impact of the STEM program on information technology college students’ goals: Perspectives from the Philippines - Catedrilla, Jypzie M. (Animo Repository, 2019)
The implementation of the K to 12 Basic Education program in the Philippines included the addition of senior high school (SHS), grades 11 and 12, which aims to equip students with skills that would help prepare them for the workplace, higher education or entrepreneurship. The Department of Education (DepEd) states that from the 1.2 million SHS graduates as of the end of SY 2017-2018, around half are expected to proceed to college. This study aims to look at the effectiveness of the SHS program, in terms of preparing the students for higher education. Specifically, the study focused on students enrolled in an information technology education (ITE) degree program and how their SHS program contributed to readiness for college. The survey method was used to the first-year college students from both private and state universities. The results of the survey show that past performance and computer self-efficacy positively influence academic goals, which in turn positively influences the technology outcome expectations. However, the results show that technology outcome expectations do not significantly influence the achievement of academic goals. © 2019 International Conference on Computers in Education, Proceedings.All right reserved.